Investigative Study of 3D Printed Connectors in Volvo Trucks production - A Comparison of Methods and Materials - Pihl, Linnea (My University, 2025)
All vehicles that are produced today by Volvo are provided with software that con trols the vehicle. In Volvo Trucks production facilities, connectors are used to download software to the vehicle by using connectors. This master thesis is carried out together with Volvo group AB and aims to conduct an investigative study to evaluate whether the connectors used could be 3D printed, used as spare parts and used in Volvo’s production. To analyze whether it is feasible to use a 3D printed connector in production, a material study was carried out, and a finite element analysis was performed on both existing and 3D printed connectors. The material study included tensile testing of the following polymer materials: Sustarine, PLA, PLA-CF, PETG, PETG-CF, TPU, and PATH-CF. In addition to tensile testing, the 3D printed test samples were also observed for surface quality and dimensional accuracy. From the material study, it was found that the PLA, PLA-CF, PETG and PETG-CF materials were suitable to print connectors in. PATH-CF was excluded due to challenges in achieving acceptable print settings and the poor surface quality it produced, and TPU was excluded due to issues such as deformation in corners and holes and insufficient layer bonding. From the finite element analysis it could be seen that all materials except TPU could be suitable to print the connectors. The TPU material was unsuitable because it was the only material in which the von Mises stress exceeded the material’s yield strength. The results indicate that it would be possible to use a 3D printed connector as a spare part. To be able to know if a 3D printed connector could have completely replaced a purchased connector, more studies would have needed to be done, such as fatigue analysis and material wear.
Keywords: 3D printing; Finite element analysis (FEA); PLA; PLA-CF; PETG; PETG-CF; TPU; PATH-CF